Self-Declaration in Halal Certification: Regulatory Loophole, Ethical Risk, or Participatory Governance Opportunity in Indonesia - Menur Kusumaningtyas; Fitri Nur Latifah (Perisai : Islamic Banking and Finance Journal, 2026)
The rapid growth of the halal industry has positioned halal certification as a crucial regulatory instrument to ensure religious compliance, consumer trust, and market integrity. The self-declaration policy for halal certification in Indonesia aims to simplify procedures and expand access for micro and small businesses. However, this policy has sparked debate regarding halal integrity, regulatory accountability, and ethical assurance. This research uses a qualitative critical legal approach with doctrinal and socio-legal analysis of regulations, policy documents, and public discourse regarding self-declaration. The analysis is conducted within the framework of the maqasid sharia and Islamic economic ethics. The results show that self-declaration improves administrative efficiency and certification access, but also poses governance risks in the form of verification gaps, weakened accountability, and a potential decline in public trust. Delegating halal claims to business actors without independent oversight risks turning halal certification into an administrative formality. Therefore, self-declaration needs to be integrated into a participatory halal governance model involving regulators, religious authorities, independent auditors, and the community. This model is considered capable of balancing regulatory efficiency, ethical integrity, and religious legitimacy. Keywords: Halal Certification, Self-Declaration, Participatory Governance, Maqasid Shariah, Islamic Economic Ethics